MENELUSURI BENANG KUSUT PERPECAHAN TAREKAT DI INDONESIA: PERSPEKTIF SEJARAH DAN SOSIAL KEAGAMAAN - Maulana, Jefri; Alfarizki, Amir; Maisyaroh (Institut Teknologi Bisnis dan Kesehatan Bhakti Putra Bangsa Indonesia, 2025)
The division in the tarekat in Indonesia is a complex phenomenon that notonly involves aspects of spirituality, but is also influenced by historical dynamicsand socio-religious contexts. This article aims to trace the roots of the division of thetarekat by exploring the historical factors and social interactions that surround it.This study uses a qualitative approach with document-based data analysis methods,in-depth interviews, and participatory observation of tarekat communities in severalregions in Indonesia. The results of the study show that the division of the order isoften triggered by differences in the interpretation of spiritual teachings inherited bythe murshids or leaders of the order. In addition, the leadership factor is also the maintrigger when the leadership transition is not collectively agreed upon by its followers.In a historical perspective, colonialism and modernization have created afragmentation of religious identity that affects the existence of the tariqat as atraditional spiritual institution. Meanwhile, from the socio-religious side, thepressure of globalization and the pluralism of religious values have widened the gapbetween the followers of the tarekat.